Collection development in the digital age (Facet Publishing, 2012)
This topical edited collection is cross-sectoral and international in scope, drawing together the perspectives of practitioners and academics at the forefront of modern collection development. They explore how practitioners can take an active role influencing strategy in this new environment, draw on case studies that illustrate the key changes in context, and consider how collection development might evolve in the future. The collection is divided into four sections looking at the key themes: The conceptual framework including a review of the literature Trends in library supply such as outsourcing and managing suppliers Trends in electronic resources including the open access movement and e-books Making and keeping your collection effectively including engaging with the user-community and developing commercial skills. Readership : LIS students and all practitioners involved in collection development and management in academic, school, public, commercial and other special libraries.